Do Osteochondroplasty Alone, Intertrochanteric Derotation Osteotomy, and Flexion-Derotation Osteotomy Improve Hip Flexion and Internal Rotation to Normal Range in Hips With Severe SCFE? - A 3D-CT Simulation Study. Issue 5 (20th May 2023) - Lerch, Till D.; Kim, Young-Jo; Kiapour, Ata; Steppacher, Simon D.; Boschung, Adam; Tannast, Moritz; Siebenrock, Klaus A.; Novais, Eduardo N.
Abstract : Background: Severe slipped capital femoral epiphysis (SCFE) leads to femoroacetabular impingement and restricted hip motion. We investigated the improvement of impingement-free flexion and internal rotation (IR) in 90 degrees of flexion following a simulated osteochondroplasty, a derotation osteotomy, and a combined flexion-derotation osteotomy in severe SCFE patients using 3D-CT-based collision detection software. Methods: Preoperative pelvic CT of 18 untreated patients (21 hips) with severe SCFE (slip-angle>60 degrees) was used to generate patient-specific 3D models. The contralateral hips of the 15 patients with unilateral SCFE served as the control group. There were 14 male hips (mean age 13±2 y). No treatment was performed before CT. Specific collision detection software was used for the calculation of impingement-free flexion and IR in 90 degrees of flexion and simulation of osteochondroplasty, derotation osteotomy, and combined flexion-derotation osteotomy. Results: Osteochondroplasty alone improved impingement-free motion but compared with the uninvolved contralateral control group, severe SCFE hips had persistently significantly decreased motion (mean flexion 59±32 degrees vs. 122±9 degrees, P <0.001; mean IR in 90 degrees of flexion −5±14 degrees vs. 36±11 degrees, P <0.001). Similarly, the impingement-free motion was improved after derotation osteotomy, and impingement-free flexion after a 30 degrees derotation was equivalent to the control group (113± 42 degrees vs. 122±9 degrees, P =0.052). However, even after the 30 degrees derotation, the impingement-free IR in 90 degrees of flexion persisted lower (13±15 degrees vs. 36±11 degrees, P <0.001). Following the simulation of flexion-derotation osteotomy, mean impingement-free flexion and IR in 90 degrees of flexion increased for combined correction of 20 degrees (20 degrees flexion and 20 degrees derotation) and 30 degrees (30 degrees flexion and 30 degrees derotation). Although mean flexion was equivalent to the control group for both (20 degrees and 30 degrees) combined correction, the mean IR in 90 degrees of flexion persisted decreased, even after the 30 degrees combined flexion-derotation (22±22 degrees vs. 36 degrees±11, P =0.009). Conclusions: Simulation of derotation-osteotomy (30 degrees correction) and flexion-derotation-osteotomy (20 degrees correction) normalized hip flexion for severe SCFE patients, but IR in 90 degrees of flexion persisted slightly lower despite significant improvement. Not all SCFE patients had improved hip motion with the performed simulations; therefore, some patients may need a higher degree of correction or combined treatment with osteotomy and cam-resection, although not directly investigated in this study. Patient-specific 3D-models could help individual preoperative planning for severe SCFE patients to normalize the hip motion. Level of Evidence: III, case-control study.